Kolonialisme as historiese proses - Klerk, P. de (Koers, 1988)
In this article the importance of viewing colonialism as a historical process is discussed. Colonialism as a historical process has certain general phases and features , as well as general causes and effects . The first phase can be called the preamble to colonization , subsequent to which the establishment of a colonial structure takes place . During the existence of this structure , which has certain general political, economic and social features , processes of change occur with in the colonial society . Which in m any cases ultimately lead to the removal o r disappearance o f the colonial structure . Usually processes of integration and of conflict and resistance are both present, but in some cases the first process and in some the other process is the dominating one . After the colonial structure has come to an end , the last phase or aftermath of the colonial process follows.